Improvement of interfacial adhesion and mechanical properties of sisal fiber‐reinforced poly(lactic acid) composites with added bisoxazoline. Issue 5 (5th January 2020) - Zhanglin, Lv; Hong wu, Wu; Yunmeng, Pei; Bi, Lan
Abstract: In order to improve interfacial adhesion between poly(lactic acid) (PLA) and sisal fibers (SFs), bifunctional monomer bisoxazoline (BO) was introduced into melt‐blending process of fibers reinforced PLA composites via in situ reactive interfacial compatibilization. The morphology of fibers and their reinforced PLA composites, thermal, and mechanical properties of the composites were studied. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) results confirmed that PLA was successfully grafted onto the surface of fiber. BO played a hinge‐like role between PLA molecular chains and SFs. The interfacial reaction and the microstructures of the SF‐reinforced PLA composites were investigated by thermal analysis. The cold crystallization temperature of the composites increased by 6.5°C with the addition of 0.6 wt% BO and 20 wt% SF as compared with the composites without BO. Microdebonding test further confirmed that interfacial shear strength of samples with BO increased by more than 30.7% in comparison with unmodified samples. For composites with 20 wt% SF addition, tensile strength and modulus increased by 34% and 10%, respectively, with 1 wt% BO addition. Flexural strength and modulus increased by 25% and 8%, respectively, with the addition of 1.2 wt% BO. Impact strength of 1 wt% BO‐modified composites was 5.1 MPa, which is 17% higher than that of the composites without BO.